Theorising indirect coercion: The logic of triangular strategies. (September 2019) - Smetana, Michal; Ludvik, Jan
This article deals with the concept of indirect coercion as a distinct type of coercive strategy involving three actors. We introduce a taxonomy of triangular strategies commonly employed in international politics: 'hostage-taking', 'patron-client' and 'composite' strategies. These three types of indirect coercion cover different ways in how the coercer draws the intermediary actor in the process of coercive bargaining to enhance his leverage over the target. For each type, we conduct a plausibility probe to study these dynamics on short empirical case studies. We argue that our conceptualisation of indirect coercion opens new avenues for research into deterrence and compellence in contemporary world politics.